A note on one decomposition of Banach spaces - Markin, M. V. (Methods of Functional Analysis and Topology, 2006)
For a scalar type spectral operator A in complex Banach space X, the decomposition of X into the direct sum equation* X=AR(A), equation* where A is the kernel of A and R(A) is the closure of its range R(A) is established.